Qualidade do sêmen canino submetido a um protocolo de congelamento rápido com adição de melatonina - Monteiro, Kianne Silva (2020)
The aim of this study are evaluate the addition of melatonin, in different concentrations, in freezing canine semen. The purpose is reducing oxidative stress, due to cryopreservation process. Six males dogs, adults, with age of two to five years were used in the study, making three semen collection, every fifteen days. The extender used was composed by Tris-egg yolk and ethylene glycol 5%, and melatonin added in the semen in five different concentrations, being a control group without addition of melatonin (T0), and the others groups with 1 mM (T1), 1,5 mM (T2), 2 mM (T3), 2,5 mM (T4) e 3 mM (T5) of melatonin. The semen was refrigerated at 4ºC for 10 minutes, after positioned 4cm above the liquid nitrogen level, until it is plunged into liquid nitrogen for cryopreservation. The semen was thawed in water bath at 37ºC for one minute and evaluated for the kinetic parameters in software CASA-SCA, morphology, membrane integrity and parameters of oxidative stress, such as catalase (CAT), superoxide dismutase (SOD), and malondialdehyde (MDA). A positive correlation were observed (p<0,05) between kinetic parameters of fresh semen (total and progressive motility, velocities curvilinear – VCL; straight-line – VSL; average path – VAP and beat cross frequency – BCF). There was no significant difference (p>0,05) in the kinetic parameters, morphology, membrane integrity, MDA or antioxidant ativity of CAT and SOD if the different treatments with melatonin are compared. There is no significant correlation (p>0,05) between sperm concentration, total protein, melatonin levels and variables related to semen quality. It was possible to evaluate the efficacy of the freezing and thawing protocol for frenchie bulldog canines, in addition to a thorough assessment about fresh semen in computer program CASA-SCA motility, defining kinetic patterns specifically for that breed. Melatonin addition in freezing canine semen didn’t provide significant increases in pos-thawing quality semen and does not decrease oxidative stress.